Partial Reinforcement of a Conditioned Emotional Response - Hilton, Anthony (My University, 1967)
Experiments were conducted, with rats, to ascertain the effects of partial reinforcement in aversive classical conditioning. Conditioned suppression of bar-pressing was more resistant to extinction following intermittent reinforcement of a conditioned stimulus than following consistent reinforcement. This effect was obtained whether or not bar-pressing was permitted during conditioning as well as during extinction. The effect was amplified by interpolating a large block of nonreinforced trials early in the partial schedule; it was eliminated by adding more reinforced trials prior to the partial schedule. The effect was not obtained by interpolating a large block of nonreinforcements in a continuous schedule. The data were related to current theoretical conceptions of partial reinforcement.
Keywords: partial reinforcement, conditioned, emotional response